Using Facebook in Improving Students’ Creative Writing Skills and Writing Motivation - SANDOY, KAREN JANE (International Journal of Language and Literary Studies, 2025)
This study aimed to use Facebook to improve students’ creative writing skills and writing motivation. This study utilized one-group pretest-posttest design to determine the effects of using Facebook in improving the students’ writing skills and writing motivation Creative Nonfiction class, a specialized subject offered to Humanities and Social Sciences (HUMSS) students. Findings of the study revealed that there is a significant difference between the creative writing skills of the students before and after using Facebook, but none between the student’s motivation levels before and after using Facebook. Additionally, based on the student’s insights, Facebook is a great way to improve their creative writing skills because of its features but can decrease their writing motivation because of its distractions. In conclusion, Facebook is useful in improving the students’ Creative Writing skills however not sufficient enough to improve their writing motivation. It is recommended to integrate accessible digital technology like social media in language learning especially in writing as students become more confident when their writing skills are showcase in front of an audience.